Aida Consumer Advertising Model On Costumer Loyalty - Rahmawati, Dian Laili; Rino, Rino (SAINTIS Publishing, 2025)
This research will try to investigate the effect of the AIDA Consumer Advertising Model on customer loyalty by using SLR (Systematic Literature Review) methodology. The AIDA Model: AIDA stands for Attention, Interest, Desire, and Action, and is used as a framework for marketing strategies. This paper reviews the relevant literature released between 2023 and 2024 and finds patterns, trends, and key outcomes on the use of the AIDA model in terms of customer loyalty. A total of 23 full text articles, which fulfilled all criteria were considered for this review. This was achieved by finding and assessing the literature on digital marketing, consumer behaviour and marketing technology in leading journals. It was noted how the model of the articles that were studied was written and the researcher adopted this part of the theoretical review after an evaluation of research methods used, theory and results of the model and model influence on customer loyalty. Results of Study An analysis of existing literature suggests that the implementation of AIDA Model provided improved customer retention by utilizing-state-of digital tactics. There were the key findings discovered from analyzed articles such as the application of AI technology in enhanced customer centric solutioning, predictive analytics for discerning marketing trends and consumer behaviors, enhanced use of social media and short-form video content to attract customer and prospect interests, the adaptation of an in-app payment service and innovative e-commerce platform for purchase acts, and lastly the ethical consideration in digital marketing for the purpose of building customer trust brand loyal. By leveraging advanced technology and innovative digital marketing strategies, the AIDA Model can be effectively integrated to enhance customer loyalty. This study makes a significant contribution to the digital marketing literature and offers practical insights for marketers aiming to enhance customer loyalty through a systematic and evidence-based approachs.